Controlling Processes Reassignment in BSP Applications - Righi, Rodrigo da Rosa; Pilla, Laércio Lima; Carissimi, Alexandre; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2008)
We have developed a model for dynamic process scheduling in heterogeneous and non-dedicated environments. This model acts over a BSP (Bulk Synchronous Parallel) application, applying runtime processes reassignment to new processors. A BSP application is divided in one or more supersteps, each one containing both computation and communication phases followed by a barrier synchronization. In this context, the developed model combines three metrics - Memory, Computation and Communication - in order to measure the potential of migration of each BSP process. The final idea is to offer a mathematical formalism involving these metrics and to decide the following questions about the process migration: When? Where? Which? This paper presents the algorithms of our model, the parallel machine organization, some experimental results and related work.